Tailoring organic electrochemical transistor through structural control and materials selection for wearable electronics and bioelectronics applications - Wu, Xihu (Nanyang Technological University, 2022)
Organic electrochemical transistors (OECTs) with the capability of transducing biological and ionic signals to electronic output have attracted significant attention in applications of bioelectronics and wearable electronics. The performance of OECTs is mainly determined by the electronic and ionic transport properties of the active layer, which heavily rely on its complex microstructures/morphology and natures of doping anions or cations. In this thesis, we focus on developing high-performance OECTs through structural control and materials selection for wearable electronics and bioelectronics applications. To enhance the practicality of employing OECTs in smart and wearable devices, we developed a self-healable PEDOT:PSS-based nanocomposite, which demonstrated remarkable self-healing as well as ion-sensing properties. Furthermore, a facile simple printing technique of spray-coating is presented to prepare active layers for OECTs, the universality of which is demonstrated for diverse substrates. These findings will contribute to the development of high performing and robust OECTs for wearable bioelectronic devices.